(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study was carried out to investigate the effect of intelligent tutor instructional strategy on students’ winding of electrical machines achievement in technical colleges in Imo State. The population of the study was 64 students in National Technical Certificate (NTC) 11. All the 64 students in National Technical Certificate (NTC) 11 was used in the study without sampling because their population size was considered manageable. The design of the study was quasi-experimental. The 64 students in National Technical Certificate (NTC) 11 used in the study were divided into experimental and control groups. Experimental group were taught with intelligent tutor instructional method while the control groups were taught with discussion and guided discovery method of instructions. The instrument used for data collection for the study was a self-structured Winding of Electrical Machines Achievement Test (WEMAT). The instrument was face and content validated by three experts. Three research questions and three hypotheses were raised. Mean statistics and standard deviation were used to answer the research questions, while Analysis of Variance (ANOVA) was used to test the null hypotheses at 0.05 level of significance. The research findings indicate that there is significant difference between the mean performance of students in the experimental group than those students in the control groups. Students taught with Intelligent Tutor instructional strategy performed better than those students exposed to discussion and guided discovery methods of instruction. Based on the findings, it was recommended among others that government should provide adequate number of computers in technical colleges so that teachers can effectively delivers their lesson using the Intelligent Tutor instructional strategy, vocational education teachers should use the Intelligent Tutor instructional strategy to teach vocational related trades in technical colleges.